Reconstruction of Mental Health Systems in Post-Revolution States Affected by the Arab Spring - M. Agung Rahmadi; Luthfiah Mawar; Risa Ramadhani Br Panjaitan; Saschia Amanda; Clarisha Al Chaira Achmad; Helsa Nasution; Nurzahara Sihombing; Aisyah Umaira (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study provides a comprehensive examination of the impact of the Arab Spring on the reconstruction of mental health systems in five major affected countries — Tunisia, Egypt, Libya, Yemen, and Syria — using a systematic review of 87 Research articles published between 2011 and 2024. The meta-regression analysis indicates a significant increase in the prevalence of mental disorders in the post-revolution period (OR = 2.87, 95% CI: 2.31–3.43, p < .001), with PTSD representing the highest proportion at 38.4%, followed by major depression at 27.6% and anxiety disorders at 24.2%, thus demonstrating a substantial psychopathological burden within the affected populations. Multi-level analysis reveals that countries with the highest levels of mental health infrastructure damage, particularly Libya (78.3%) and Syria (72.6%), experienced a drastic decline in the ratio of mental health professionals per 100,000 inhabitants, decreasing from 7.8 to 2.1, marking a severe limitation in service capacity. These findings expand upon the Research of Spagnolo et al. (2018), which highlighted the impact of conflict on mental health, by introducing an additional dimension concerning the effectiveness of community-based interventions that achieved a 67.8% success rate (p < .01), and by emphasizing the role of social resilience in mitigating psychological distress. Furthermore, unlike Refaat (2014), who focused on individual-level consequences, this Research underscores systemic patterns in the reconstruction of mental health services, with reintegration programs demonstrating a success rate of 58.4% (95% CI: 51.2–65.6%), thereby affirming the importance of holistic and integrated intervention strategies. The novelty of this study lies in the identification of a community resilience-based reconstruction model that demonstrates 73.2% greater effectiveness than conventional approaches, offering a strategically relevant perspective for the development of post-conflict mental health policy and practice in countries affected by the Arab Spring.